2015
DOI: 10.5888/pcd12.140229
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Prevalence of Overweight or Obese Children and Adolescents in Small Geographic Areas Using Publicly Available Data

Abstract: IntroductionInterventions for pediatric obesity can be geographically targeted if high-risk populations can be identified. We developed an approach to estimate the percentage of overweight or obese children aged 2 to 17 years in small geographic areas using publicly available data. We piloted our approach for Georgia.MethodsWe created a logistic regression model to estimate the individual probability of high body mass index (BMI), given data on the characteristics of the survey participants. We combined the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…Priority areas that cover 80% of the overweight or obese children in Georgia, as estimated using approaches described in Davila Payan et al [34]. Georgia, as estimated in the approach described in Davila Payan et al [34]. The method was validated by comparing it to school examination data in Arkansas, and we found that it generally performed well.…”
Section: Chronic Diseasesmentioning
confidence: 79%
See 2 more Smart Citations
“…Priority areas that cover 80% of the overweight or obese children in Georgia, as estimated using approaches described in Davila Payan et al [34]. Georgia, as estimated in the approach described in Davila Payan et al [34]. The method was validated by comparing it to school examination data in Arkansas, and we found that it generally performed well.…”
Section: Chronic Diseasesmentioning
confidence: 79%
“…A different aspect of obesity has been considered by Davila Payan et al [34]. Public health practitioners were interested in intervening to reduce overweight or obesity prevalence among children and youths.…”
Section: Chronic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our geographically detailed maps provide actionable evidence of where to geographically target interventions by identifying which neighborhoods experience the worst health outcomes. [13] These findings can also spur investigations of what specific health challenges these geographic areas face, which can help shape the interventions for minority communities that face the highest health disparities. [14] …”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous statements and the literature you can find in many studies working the obesity influence factors, they have implemented several data mining techniques as you can find in (Davila-Payan et al, 2015;Manna and Jewkes, 2014;Adnan and Husain, 2012;Adnan et al, 2010;Dugan et al, 2015;Zhang et al, 2009;Suguna, 2016;Abdullah et al, 2016). Data mining is a discipline that studies massive data sources, with the objective of obtaining new information from it, to support decision making.…”
Section: Introductionmentioning
confidence: 99%